2019
DOI: 10.1001/jamanetworkopen.2019.0393
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Employee Susceptibility to Phishing Attacks at US Health Care Institutions

Abstract: Key Points Question Are employees at US health care institutions susceptible to phishing attacks? Findings In this multicenter quality improvement study, more than 2.9 million simulated emails were sent to employees at 6 hospitals, with a median click rate of 16.7%. Repeated phishing campaigns were associated with decreased odds of clicking on a subsequent phishing email. Meaning Employees at US health care institutions may be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 9 publications
(21 reference statements)
1
57
0
1
Order By: Relevance
“…Importantly, a mandatory training programme did not have any significant effect, with those previously scammed remaining more likely to click on a phishing email, suggesting that targeted staff training may be required 22. The second paper was a retrospective, multicentre study of six US healthcare institutions that ran phishing simulations from 2011 to 2018 and reported that of around 3 million phishing emails, around 400 000 (14%) were clicked, but in this study, repeated phishing campaigns were associated with reduced odds of clicking on subsequent phishing emails 23…”
Section: Discussionmentioning
confidence: 69%
“…Importantly, a mandatory training programme did not have any significant effect, with those previously scammed remaining more likely to click on a phishing email, suggesting that targeted staff training may be required 22. The second paper was a retrospective, multicentre study of six US healthcare institutions that ran phishing simulations from 2011 to 2018 and reported that of around 3 million phishing emails, around 400 000 (14%) were clicked, but in this study, repeated phishing campaigns were associated with reduced odds of clicking on subsequent phishing emails 23…”
Section: Discussionmentioning
confidence: 69%
“…Due to COVID-19 restrictions, the selection meeting of the IMIA Yearbook Editorial Committee was held as a videoconference on Apr 17, 2020. In this meeting, three papers [6][7][8] were finally selected as best papers for the CIS section (Table 2). A content summary of these three CIS best papers can be found in the appendix of this synopsis.…”
Section: About the Paper Selectionmentioning
confidence: 99%
“…The last of the best papers comes from William J. Gordon and colleagues [7], who investigated health care employees' susceptibility to phishing attacks. This study can be assigned to both clusters, and should all of us remember that cybersecurity is increasingly critical and should be tackled accordingly.…”
Section: Findings and Trends In 2019mentioning
confidence: 99%
“…Health care organizations are especially vulnerable to information security threats, as data breaches can have direct and severe consequences on patients' lives [2][3][4]. Attacks against hospitals have been increasing in both number and level of sophistication [5].…”
Section: Introductionmentioning
confidence: 99%
“…Phishing poses a major cybersecurity risk for 2 reasons: (1) employees usually have detailed knowledge about IS within the organization and access the data frequently during their work and (2) even 1 innocent click could expose the organization to a network of hackers nearly impossible to trace [9][10][11][12]. A recent study analyzed phishing campaigns in health care organizations and found that, on average, as much as 14.2% of these phishing emails were clicked on by employees [5]. Organizations have taken steps to address this problem by providing training programs to educate and increase cybersecurity awareness, but these efforts remain insufficient.…”
Section: Introductionmentioning
confidence: 99%